An Empirical Examination of the Form of the Relationship Between Multinationality and Performance - Gomes, Lenn; Ramaswamy, Kannan (Journal of International Business Studies, 1999)
This paper reports findings from a study that systematically evaluated the form of the relationship between multinationality and performance. In contrast to most of the prior conceptualizations that rely on linear, monotonic models of the linkage, this study examined a curvilinear model that addresses both the costs and benefits associated with multinationality. It used time-series techniques to capture both the static and dynamic components of the relationship. Results show that increasing levels of multinationality bring significant performance benefits up to a certain optimum level beyond which benefits begin to decelerate, while costs accelerate.